Analysis of Promotion and Service Quality on Decisions to Use Auto2000 Service Services Waru Branch - Nurtalia, Athaillah Cindra; Nugroho, Rusdi Hidayat (Business and Investment Review, 2024)
This study aims to analyze the effect of promotion and service quality on decisions to use service services at Auto2000 Waru Branch. In an increasingly competitive business world, it is important for automotive companies such as Auto2000 to understand the factors that influence consumer decisions. The method used in this research is descriptive qualitative, where data is collected through interviews with customers and employees. The results show that attractive promotions, such as discounts and loyalty programs, as well as the use of social media, are very influential in attracting customer attention. addition, friendly, fast, and professional service quality is also a key factor in creating customer satisfaction. Customers value efficient turnaround times and the staff's ability to explain the service process well. By combining effective promotional strategies and quality service, Auto2000 Waru Branch can attract more customers and maintain the loyalty of existing customers. This study recommends that Auto2000 continue to innovate in marketing strategies, improve training for employees, and expand promotional programs to better suit customer needs. It is hoped that the results of this study can make a positive contribution to the development of after-sales services in the automotive industry in Indonesia.